Job Satisfaction and Work Engagement in the Workplace, A Systematic Review for the Period 2019-2024 - Aguirre-Camarena, Richard; Aguilar Doñe, Brisa Cielo; Manchego Guerra, José Renatto; Barraza Lino, Roberto Pablo; Rengifo Villanueva, Ronald (LACCEI, 2025)
The purpose of this study is to present the state of the art regarding the theoretical aspects of the variable Job Satisfaction associated with the variable Work Engagement in the business environment. The literature on the subject is reviewed from the perspective of various authors within the scientific community, where job satisfaction is referred to as a positive emotional state resulting from an individual's perception of their work and environment, linked to indicators such as work climate and job performance. On the other hand, work engagement is considered a state of involvement, vigor, and absorption in work and has been identified as a mediator between motivation and organizational outcomes. The methodology employed is a systematic review of research using the PRISMA method, selecting a total of 22 studies published between 2019 and 2024. Additionally, the search and analysis of scientific articles were conducted through the Scopus database. The discussion presents different perspectives on the impact of the subject. It is concluded that there is a strong relationship between job satisfaction and work engagement across different sectors and organizational contexts, significantly influencing employee well-being and thereby ensuring a positive impact on both individual performance and organizational stability.